Системы охлаждения компрессорных установок - Берман Я. А. Яков Аронович; Маньковский О. Н. Олег Николаевич; Марр Ю. Н. Юрий Николаевич; Рафалович А. П. Александр Пинхусович (Ленинград, Машиностроение, 1984)
Авт. указ. на обороте тит. л.